Sexual satisfaction after child birth: vaginal versus elective cesarean delivery - Hantoushzadeh S (Tehran University Medical Journal, 2009)
"nBackground: The perception of impairment of sexual function after childbirth in vaginal delivery (as a complication) makes pregnant women to request elective cesarean section. But this conception is more related to culture. Therefore we studied women's sexual health after childbirth to assess whether women who underwent cesarean section experienced better sexual health in the postnatal period than women with vaginal births. "nMethods: A cohort study was conducted on 303 primiparous women who had delivered vaginaly and 315 primiparous delivered by elective cesarean section in seven private hospitals in Tehran, employing data of demographic characteristics like age, education, BMI, obstetric history (weight gain in pregnancy, history of pelvic pain and vaginal discharge), stress incontinence history (prepregnancy and during pregnancy) and effect of delivery on sexual satisfaction in several follow-ups until 12 months after delivery. "nResults: Sexual satisfaction after delivery in vaginal group was significantly more than cesarean group. (76% vs 60%, p<0.0001). There was no relation between pelvic pain & delivery type (in several follow- up). "nConclusions: Instead of social conception of have more sexual satisfaction after cesarean delivery, outcomes from this study provide no basis for advocating cesarean section as a way to protect women's sexual function after childbirth. Therefore Request of cesarean section by mother for having more sexual satisfaction after childbirth is not logic.